Quantum mechanical and experimental infra-red studies on stability and structural properties of substituted acylthiourea compounds - Ghebreysus Woldu, Mengistu (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2004.